2016
DOI: 10.1097/nmd.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Inner Speech and Clarity of Self-Concept in Thought Disorder and Auditory-Verbal Hallucinations

Abstract: Eighty patients and thirty controls were interviewed using one interview that promoted personal disclosure and another about everyday topics. Speech was scored using the Thought, Language and Communication scale (TLC). All participants completed the Self-Concept Clarity Scale (SCCS) and the Varieties of Inner Speech Questionnaire (VISQ). Patients scored lower than comparisons on the SCCS. Low scores were associated the disorganized dimension of TD. Patients also scored significantly higher on condensed and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 96 publications
8
30
3
Order By: Relevance
“…the marginally significant reduction in dialogicality in the inner speech reported by Langdon, Jones, Connaughton, & Fernyhough, 2009 ). In contrast, a recent study with a clinical sample suggested that condensed and other people in inner speech were related to psychopathology ( de Sousa et al, 2016 ). As a potential explanation of these disparate findings, dialogic inner speech is typically the factor that correlates most with all of the other VISQ factors; this is also the case with the findings reported here.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…the marginally significant reduction in dialogicality in the inner speech reported by Langdon, Jones, Connaughton, & Fernyhough, 2009 ). In contrast, a recent study with a clinical sample suggested that condensed and other people in inner speech were related to psychopathology ( de Sousa et al, 2016 ). As a potential explanation of these disparate findings, dialogic inner speech is typically the factor that correlates most with all of the other VISQ factors; this is also the case with the findings reported here.…”
Section: Discussionmentioning
confidence: 92%
“…In general, condensed inner speech scores also show few correlations with non-VISQ variables ( Ren et al, 2016 ). As noted above, there is evidence that patients with psychosis endorse this experience more than controls, and that it relates to increased levels of thought disorder ( de Sousa et al, 2016 ). As such, it would seem to be an important factor to retain and may be more informative when used in clinical samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, we have reported previously that difficulties in internal source monitoring (ability to correctly discriminate whether self-generated cognitions were verbalised or just thought) 93 coupled with negative affect are important to explain exacerbation of thought disorder during emotional challenge, 75 and that poverty of speech seems to be specifically associated with impoverished inner speech (especially dialogical inner speech). 35 Finally, how these mechanisms relate to important social predictors of thought disorder remains a matter of speculation. Some authors have suggested that difficulties recognising and reasoning about mental states in patients diagnosed with schizophrenia spectrum disorders could be a consequence of early experiences such as poor early attachments, childhood trauma or isolation, 94 factors that have been found to be associated with thought disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Thought disorder assessment scales, such as the Scale for the Assessment of Thought, Language and Communication Disorders (TLC) 31 or the Thought Language Index, 32 distinguish between poverty of speech and disorganisation items, and such differentiation has been further supported by factor analytical studies 33 and studies on the psychological mechanisms of both positive and negative thought disorder. 34,35 Many studies have used measurements obtained by general psychopathology scales (e.g. Positive and Negative Syndrome Scale (PANSS) 36 or the Brief Psychiatric Rating Scale (BPRS) 37 ) to test hypotheses about the mechanisms involved in thought disorder.…”
Section: Thought Disorder and Cognitive Disorganisationmentioning
confidence: 99%